Roles of multiple glucose transporters in Saccharomyces cerevisiae. - Ko, C H (1993)
In Saccharomyces cerevisiae, TRK1 and TRK2 are required for high- and low-affinity K+ transport. Among suppressors of the K+ transport defect in trk1 delta trk2 delta cells, we have identified members of the sugar transporter gene superfamily. One suppressor encodes the previously identified glucose transporter HXT1, and another encodes a new member of this family, HXT3. The inferred amino acid sequence of HXT3 is 87% identical to that of HXT1, 64% identical to that of HXT2, and 32% identical to that of SNF3. Like HXT1 and HXT2, overexpression of HXT3 in snf3 delta cells confers growth on low-glucose or raffinose media. The function of another new member of the HXT superfamily, HXT4 (previously identified by its ability to suppress the snf3 delta phenotype; L. Bisson, personal communication), was revealed in experiments that deleted all possible combinations of the five members of the glucose transporter gene family. Neither SNF3, HXT1, HXT2, HXT3, nor HXT4 is essential for viability. snf3 delta hxt1 delta hxt2 delta hxt3 delta hxt4 delta cells are unable to grow on media containing high concentrations of glucose (5%) but can grow on low-glucose (0.5%) media, revealing the presence of a sixth transporter that is itself glucose repressible. This transporter may be negatively regulated by SNF3 since expression of SNF3 abolishes growth of hxt1 delta hxt2 delta hxt3 delta hxt4 delta cells on low-glucose medium. HXT1, HXT2, HXT3, and HXT4 can function independently: expression of any one of these genes is sufficient to confer growth on medium containing at least 1% glucose. A synergistic relationship between SNF3 and each of the HXT genes is suggested by the observation that SNF2 hxt1 delta hxt2 delta hxt3 delta hxt4 delta cells and snf3 delta HXT1 HXT2 HXT3 HXT4 cells are unable to grow on raffinose (low fructose) yet SNF3 in combination with any single HXT gene is sufficient for growth on raffinose. HXT1 and HXT3 are differentially regulated. HXT1::lacZ is maximally expressed during exponential growth whereas HXT3::lacZ is maximally expressed after entry into stationary phase.